Fight without sight: The contribution of vision to judo performance - Krabben, K. J.; van der Kamp, J.; Mann, D. L. (Psychology of Sport and Exercise, 2018)
Objective: Although vision is typically considered the predominant sense for guiding performance, there are sports for which other senses are believed to be as important, if not more important than vision. Accordingly, in Paralympic judo, athletes with different degrees of vision impairment (VI) compete together based on the assumption that vision does not influence judo performance, as long as judokas start the match with their grip in place. The aim of this research was to test this assumption. Method: We conducted two studies. In the first we analysed data from two major recent VI judo competitions to compare the relative performance of blind and partially sighted athletes when competing against each other. In the second study, twenty-four able-sighted players competed in practice matches in sighted and blindfolded conditions. Results: In Study 1, we demonstrated that blind judokas win far less medals in VI judo competitions than their partially sighted opponents. In study 2, a significant performance advantage was found for sighted judokas fighting against blindfolded opponents. Conclusions: Vision enhances judo performance, even when judokas start the match with their grip in place. These findings suggest that it would be desirable to take measures to make VI judo competition fairer to those who are most severely impaired.